Efektivitas Peran Bappeda Dalam Perencanaan Pendapatan Asli Daerah (PAD) Di Kabupaten Aceh Barat Daya - Yusnira, Desi; Sartika, Dewi (Jurnal Ilmiah Akuntansi Kesatuan, 2024)
Increasing PAD (Pendapatan Asli Daerah) or local original income will have a good influence on increasing regional development and development. The better the contribution of PAD to the APBD (Anggaran Pendapatan dan Belanja Daerah), the less the government's fiscal dependence will be. This research was conducted to find out how effective the role of Bappeda is in planning local revenue in Southwest Aceh Regency. The type of research used is qualitative research with descriptive analysis method, which is research that refers to the preparation of theories formed by collecting data, compiling data, and analysing data. The data used in this study were sourced from primary and secondary data, which were obtained through observation and interviews. The results of the study concluded that in general the role of the Regional Development Planning Agency of Southwest Aceh Regency in Planning for Regional Original Revenue (PAD) is included in the criteria very effective, this can be seen from the average value of the effectiveness level of regional original revenue revenue of Southwest Aceh Regency during 2019 to 2022 which is 107.51%.